CLASSIFICATION OF MPN - Haifa Kathrin Al-Ali (Hematology, Transfusion and Cell Therapy)
The 2022 updated 5th edition of the World Health Organization Classification of myeloproliferative neoplasms and mastocytosis focused on changes in the rationale behind the classification, combined morphologic, immunophenotypic, molecular, and cytogenetic data that help to refine diagnostic criteria and emphasize therapeutically and/or prognostically actionable biomarkers. While a genetic basis for defining diseases is sought where possible, the classification strives to keep practical applicability in perspective. In addition, a new International Consensus Classification (ICC) has been introduced for myeloid neoplasms and acute leukemia. In the context of MPN, the classical subtypes of MPN remained unchanged; however, the experts made an effort to refine the diagnostic criteria to allow a distinction between subtypes. With refinement of the diagnostic criteria, the hope is that clinicians will be able to distinguish between specific subtypes with greater accuracy and present a more definitive and holistic management for patients from diagnosis through disease monitoring.